2017
DOI: 10.1158/1538-7445.am2017-88
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 88: The role of RBPMS in cisplatin resistant ovarian cancer

Abstract: Epithelial ovarian cancer is the fifth leading cause of cancer-associated deaths among women in the United States. High-grade serous ovarian cancer (HGSOC) is the most common type of epithelial ovarian cancer and accounts for 70-80% of ovarian cancer patient deaths. RNA-Binding Protein With Multiple Splicing (RBPMS) is a member of a family of proteins that bind to the nascent RNA transcripts and regulate their processing, including the pre-mRNA splicing and the transport, localization, and stability of the RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Multiple studies implicate RBPMS in some aspect of ovarian cancer pathogenesis and in the biology of other human cancers. RBPMS is over-expressed in the A2780 cervical cancer cell line and depletion of RBPMS in A2780 cells using small interfering RNA (siRNA) resulted in an increase in invasive potential, while over-expression of RBPMS in cisplatin-resistant A2780CP20 cells resulted in decreases in cell proliferation 15 . A study identifying differentially expressed genes between recurrent and non-recurrent ovarian cancer found that RBPMS was among the most differentially expressed genes (DEGs) between these groups and formed a node when generating a protein-protein interaction network based on interaction between DEGs (16).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies implicate RBPMS in some aspect of ovarian cancer pathogenesis and in the biology of other human cancers. RBPMS is over-expressed in the A2780 cervical cancer cell line and depletion of RBPMS in A2780 cells using small interfering RNA (siRNA) resulted in an increase in invasive potential, while over-expression of RBPMS in cisplatin-resistant A2780CP20 cells resulted in decreases in cell proliferation 15 . A study identifying differentially expressed genes between recurrent and non-recurrent ovarian cancer found that RBPMS was among the most differentially expressed genes (DEGs) between these groups and formed a node when generating a protein-protein interaction network based on interaction between DEGs (16).…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin is one of the most important anticancer compounds used in the first line of chemotherapy for the treatment of ovarian cancer (15). Resistance to chemotherapeuic drugs including cisplatin, is a hindrance to successful chemotherapy in the patients with ovarian cancer (16,17). Therefor, new modalities are needed to overcome drug resistance (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to chemotherapeuic drugs including cisplatin, is a hindrance to successful chemotherapy in the patients with ovarian cancer (16,17). Therefor, new modalities are needed to overcome drug resistance (17,18). VPA is a short chain fatty acid which is used in the treatment of various neurological disorders including seizures, bipolar disorder, and migraine (19).…”
Section: Discussionmentioning
confidence: 99%